2008
DOI: 10.1073/pnas.0707140104
|View full text |Cite
|
Sign up to set email alerts
|

Booster vaccination of cancer patients with MAGE-A3 protein reveals long-term immunological memory or tolerance depending on priming

Abstract: We previously reported results of a phase II trial in which recombinant MAGE-A3 protein was administered with or without adjuvant AS02B to 18 non-small-cell lung cancer (NSCLC) patients after tumor resection. We found that the presence of adjuvant was essential for the development of humoral and cellular responses against selected MAGE-A3 epitopes. In our current study, 14 patients that still had no evidence of disease up to 3 years after vaccination with MAGE-A3 protein with or without adjuvant received an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 54 publications
5
107
1
1
Order By: Relevance
“…Collectively, these findings indicate that T-cell-based immunotherapies might represent one therapeutic route for effective targeting of CT antigens. Importantly, immunization with MAGE-A3 protein has previously been performed in melanoma and lung cancer patients and has proven to be safe, to be capable of evoking specific humoral and T-cell responses, 47,48 and to have some clinical activity in patients in the adjuvant setting. 49 However, in addition to applying immunotherapy directed against MAGE-C1/CT7 or MAGE-A3 these genes might also be targeted by more "immediate" therapeutic modes such as small molecules, antisense oligonucleotides, or classical gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these findings indicate that T-cell-based immunotherapies might represent one therapeutic route for effective targeting of CT antigens. Importantly, immunization with MAGE-A3 protein has previously been performed in melanoma and lung cancer patients and has proven to be safe, to be capable of evoking specific humoral and T-cell responses, 47,48 and to have some clinical activity in patients in the adjuvant setting. 49 However, in addition to applying immunotherapy directed against MAGE-C1/CT7 or MAGE-A3 these genes might also be targeted by more "immediate" therapeutic modes such as small molecules, antisense oligonucleotides, or classical gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, CT7-specific CD4 + T cells were able to specifically kill peptide-pulsed melanoma cell line in a chromium release assay. Perforin-secreting CD4 + T cells have been previously described for the in vitro expanded MAGE-A3-specific CD4 + T cells (14) and in vivo for viral antigen-specific CD4 + T cells (38). Recently, two murine studies showed that cytolytic tumor-specific CD4 + T cells can egress to the tumor site and efficiently eradicate melanoma lesions when combined with additional treatments (39,40).…”
Section: Ct7-specific Cd4 + T-cell Clones Recognize Naturally Processmentioning
confidence: 99%
“…Spontaneous immunity to CT antigens was found in melanoma patients, which illustrates their immunogenicity (8,9). Boosting the tumor-specific immune response is considered a promising therapeutic modality with minimal toxicity, and promising results have been achieved with this approach (10)(11)(12)(13)(14). Ideally, an effective antitumor vaccine consists of immunogenic tumor-specific antigens, such as NY-ESO-1 (15).…”
mentioning
confidence: 99%
“…In vitro stimulation (presensitization) of T cells from ovarian cancer patients, who had spontaneous Ab against NY-ESO-1, was performed as described (29). Briefly, CD8…”
Section: Presensitizationmentioning
confidence: 99%